2000
DOI: 10.1093/fampra/17.6.490
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a patient record-based risk model for recurrent falls among elderly people living in the community

Abstract: A risk model consisting of six variables usually known to the GP from the patient records may be a useful tool in the identification of elderly people living in the community at risk for recurrent falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 32 publications
6
28
0
5
Order By: Relevance
“…In these studies, the risk of subsequent falls was increased twofold to threefold [10, 12, 16, 17, 25-27, 30, 32], also consistent with the magnitude of the increased risk of falls in NORA. Other clinical risk factors identified in NORA were identified in previous studies of communitydwelling elderly populations, including depression [16,17,42] and stroke [10,13,14,20], which increased the odds of any fall in NORA by 43% and 39%, respectively. In one study [17], depression was one of four factors predictive of recurrent falls.…”
Section: Concurrence With Prior Studies Of Fall Riskmentioning
confidence: 66%
See 2 more Smart Citations
“…In these studies, the risk of subsequent falls was increased twofold to threefold [10, 12, 16, 17, 25-27, 30, 32], also consistent with the magnitude of the increased risk of falls in NORA. Other clinical risk factors identified in NORA were identified in previous studies of communitydwelling elderly populations, including depression [16,17,42] and stroke [10,13,14,20], which increased the odds of any fall in NORA by 43% and 39%, respectively. In one study [17], depression was one of four factors predictive of recurrent falls.…”
Section: Concurrence With Prior Studies Of Fall Riskmentioning
confidence: 66%
“…Arthritis of the hip was a risk factor for injurious falls in another study of community-dwelling women aged 75 and older [18]. Pain or stiffness in muscles and joints was found to double the risk of recurrent falls in persons aged 70 and older [42].…”
Section: Concurrence With Prior Studies Of Fall Riskmentioning
confidence: 92%
See 1 more Smart Citation
“…There is no agreement between researchers for which tests are more appropriate in a specific situation 54 . Most tools rely on assessments of balance and strength [55][56][57][58][59][60] , so there are not applicable in the primary care settings.…”
Section: Predicting the Risk Of Fallmentioning
confidence: 99%
“…It is reported both by elderly people who experienced a fall and by those who have no previous fall experience [1][2][3][4]. Studies conducted in the US, UK and The Netherlands report about 20-60% of the older people living in the community experiencing at least some fear of falling [2,3,[5][6][7][8][9][10][11]. In two studies an even higher percentage of elderly people who reported fear of falling was observed [12,13].…”
Section: Introductionmentioning
confidence: 99%